The salafi da’wa movement in Jakarta from the perspective of media glocalization - Fakhrullah, Andi; Bakti, Andi Faisal; Hermansah, Tantan; Fanshoby, Muhammad (IJISH (International Journal of Islamic Studies and Humanities), 2023)
Salafi is a transnational Islamic movement. In Indonesia, the spread of Salafism is influenced by graduates from the Middle East. As a conservative movement, the Salafi community in Jakarta has been different from its early days. Today they are a movement that enjoys modernity and negotiates its ideology. This research aims to investigate and analyze the occurrence of glocalization on the global ideology of the Salafi movement with local aspects in Jakarta, and to what extent this glocalization influences the transformation of their dakwah media to localize their ideology for acceptance on a local scale. This research uses the theory of glocalization through media by Jan Servaes and Rico Lie. The first concept of glocalization through media theory explains it from a transformationalist perspective. Second, this theory explains hybridization in glocalization. Third, it explains globalization, localization, and cultural identity. The three concepts in this theory become a reference in research related to the Salafi da’wah movement in Jakarta. The results of the discussion and analysis of the glocalization media of the Salafi da’wah movement in Jakarta show that in responding to globalization, the Salafi community at the Nurul Iman Blok M Square Mosque is transformationalist. They hybridize their global ideology by negotiating the Pancasila ideology which is a local ideology so that the process of glocalization of da’wah can be accepted by the local community. Through the media, one of their preachers also hybridizes ideology with a display that represents local symbols by wearing a black skullcap or national cap that is identical to the Indonesian cultural cap. Salafi communities in Jakarta also hybridize their fundamental ideology with media products as global or Western products in the context of media glocalization.